HAND LINE CATCHES COMPOSITION LANDED AT CILACAP OCEANIC FISHING PORT - Muhammad Salman Alfarizi Mubarok; Nora Akbarsyah (Jurnal Penelitian Perikanan Laut (Albacore), 2026)
Hand line fishing gear is one of the fishing gears actively operated at the Cilacap Ocean Fisheries Port (PPS). This gear is included in the selective fishing gear category, because it only catches target species and has a very low risk of bycatch or damage to seabed habitats. The purpose of this study was to identify and analyze the composition of fish catches and the frequency of fishing vessels at the Cilacap PPS. This research was conducted in July–August 2025 using direct observation and interview methods. The research results were then processed using the Shannon-Wiener diversity index formula. Uniformity analysis was processed by referring to research conducted by Sirait et al. (2018), and dominance analysis used the Simpson index formula. Based on the results of this study, the total catch of hand line fishing gear in July reached 1,663,912 kg. The catch was dominated by yellowfin tuna with a weight of (432.629 kg) and rubber squid with a weight of (382.734 kg), in addition to other species such as bigeye tuna, ribbonhead, albacore, lemadang, and swordfish. Based on the analysis results, the diversity index value is 2.01, the uniformity index is 0.18, and the dominance index is 0.61. This variation in catch results is influenced by oceanographic conditions, fish migration behavior, and the availability of resources in the fishing area. The fleet is dominated by large vessels (20-30 GT) which reflects efficiency in reaching fishing areas and a larger load capacity. The hand line fishing gear used has proven to be selective with low bycatch and is environmentally friendly, thus supporting the principles of sustainable fisheries management. Key words: catch composition, Cilacap Oceanic Fishing Port, hand line, pelagic fish, sustainable fisheries